Islamic Moderation in Conflict Resolution: Yusuf Al-Qardhawi’s Perspectives and Their Contribution to Campus Life at Universiti Utara Malaysia - Rizza, Muhamad; Aprial, Bayu Jonida; Muhibbi, Moh. Saddad; Nurhakim, Dede Arif Rahman (Fakultas Tarbiyah dan Ilmu Keguruan (FTIK) UIN Sayyid Ali Rahmatullah Tulungagung, 2025)
Purpose – This research investigates Yusuf Al-Qardhawi’s conceptualization of Islamic moderation (wasatiyyah) and examines its relevance in promoting interfaith understanding and social cohesion within the academic environment of Universiti Utara Malaysia. The study addresses the growing need for moderate Islamic discourse in managing diversity and fostering peaceful coexistence on campus Methods – qualitative approach combining a systematic literature review and case study methodology was employed. Literature was sourced from Scopus using the keywords Yusuf Al-Qaradawi, Religious Moderation, and Islamic Tolerance. Article selection followed PRISMA guidelines with bibliometric analysis via VOSviewer and quality assessment using Harzing’s Publish or Perish. Mendeley supported reference management to ensure transparency and rigor Findings – The findings reveal that Al-Qardhawi’s moderation—rooted in balance, justice, and tolerance—can guide universities in promoting respectful interreligious engagement. Applied in academic settings, these principles encourage inclusive dialogue, mutual respect, and cultural harmony among diverse student and faculty populations Limitations – The study is limited to literature-based analysis without empirical interviews or field observations within the university. Value – This research provides actionable insights for integrating Islamic moderation into campus policies and curricula, contributing to a more cohesive, inclusive, and culturally sensitive academic environment.